Interface induced magnetic properties of Gd/Co heterostructures. Issue 33 (10th August 2018) - Basha, M. A.; Prajapat, C. L.; Gupta, M.; Bhatt, Harsh; Kumar, Yogesh; Ghosh, S. K.; Karki, V.; Basu, S.; Singh, Surendra
Abstract : Correlation of the interface structure and magnetization of Gd/Co multilayers on annealing at 400 °C. Abstract : Antiferromagnetic coupling between rare-earth and transition metal ferromagnetic layers gives rise to various magnetic ground states in heterostructures of these materials. Interface structure and morphology tend to play important roles in magnetic properties of such systems. Interface induced magnetization in Gd/Co heterostructures has been studied using a combination of structural and magnetic characterization techniques. The interface morphology of the Gd/Co system was varied by growing Gd/Co multilayers using magnetron sputtering under different argon partial pressures. Interfacial properties were further modified by annealing the multilayers under high vacuum. The macroscopic magnetization measurements have been correlated with depth dependent structure and magnetic properties of multilayers studied using X-ray and polarized neutron reflectometry techniques. Secondary ion mass spectrometry measurements from both as-deposited and annealed samples also confirmed modification at the interfaces. It has been shown that the interface structure, together with roughness, leads to a unique low-temperature magnetic phase characterized by twisting of Gd and Co moments.